Strategic Management of Professional Service Firms Theory and Practice - Kaiser, Stephan; Ringlstetter, Max Josef (Springer Berlin Heidelberg, 2011)
Managing strategies for professional service firms is an important and complex activity. The main issues in this book cover the core management principles for service firms in a comprehensive way. Based on current research findings it includes the management of service quality, knowledge and marketing as well as people, organizational and strategic issues. In understanding critical resources managers and partners will be able to effectively develop and exploit them. The book contains practical advice and offers a profound insight into the managerial excellence of service companies.